Mosque and Civilization: Setting Islamic Center of Nusa Tenggara Barat as Center of Civilization - Dedy Wahyudin (NALAR, 2020)
This article aims to describe the meaning, current state, challenges, and projection of the Islamic center of West Nusa Tenggara Province of Indonesia as the center of civilization. The scope of the study is all fields of civilization ranging from spiritual, education, social services, economic to public policies domain. This scope is referring to what Prophet Muhammad peace be upon him did with an-Nabawi grand mosque in al-Madinah al-Munawwarah as the center of the first generation of Muslims’s life starting from private to public life. The method used in this research is qualitative research with a phenomenological approach as a paradigm. As a conclusion, it could be said that this Islamic center has been completing landscape of Lombok Island as an island of thousand mosques, proofing compatibility of Islam with modernity, promising the wider and more important roles of the center to recall Islamic civilization as the machine of Muslims movement at all aspects of life and contribute to building a better world for all human beings all over the world.Keyword : Mosque, Islamic Centre, Islamic Civilization.